Impact of the fast track land reform on rural poverty in Masvingo District in Zimbabwe - Matunhu, Jephias (Midlands State University, 2014)
This study investigated the effect of the fast track land reform in addressing the poverty crisis in Masvingo district. The study targeted those rural residents who did not benefit land during the fast track land reform. The target population was the poor people who live in Masvingo area. The study triangulated the qualitative and quantitative research designs. The theoretical framework of the study is the revisionist theory which suggests that rural agriculture is a solution to the poverty crisis in rural communities. The study concluded that the agro-based land reforms in Zimbabwe did not reduce household poverty in Mushandike. The study recommended, among other things, the application of the sustainable rural development framework for analysis model to improve the livelihoods of the farmers who did not move over to occupy new land in the resettlement areas.